Acute Changes in Left Atrial Pressure After MitraClip Are Associated With Improvement in 6-Minute Walk Distance. (April 2017) - Maor, Elad; Raphael, Claire E.; Panaich, Sidakpal S.; Reeder, Guy S.; Nishimura, Rick A.; Nkomo, Vuyisile T.; Rihal, Charanjit S.; Eleid, Mackram F.
Abstract : Background—: Data on the clinical use of left atrial (LA) hemodynamic monitoring during MitraClip procedure are limited. This study evaluated the association between intraprocedural changes in LA pressure after MitraClip and improvement in exercise capacity as documented by 6-minute walk test (6MWT). Methods and Results—: Study population included 50 patients who underwent MitraClip at the Mayo Clinic (Rochester, MN), between June 2014 and July 2016 and completed both baseline and 30-day follow-up 6MWT. Primary outcome for the current analysis was defined as 6MWT improvement above the median. Mean age of the study population was 79±10 years, and 34 (68%) were men. Baseline preprocedural 6MWT distance was 308 m (interquartile range [IQR], 234–394 m). Acute, intraprocedural change in LA pressure after MitraClip was 3 mm Hg (IQR, 1–6 mm Hg), and change in V wave was 11 mm Hg (IQR, 6–19 mm Hg). Median 6MWT improvement was 25 m (IQR, 19–47 m). Univariate analysis showed that patients with ⩽ mild postprocedural mitral regurgitation were 4-fold more likely to experience an improvement in 6MWT ( P =0.02). Multivariate model demonstrated that each 5 mm Hg decrease in V wave was associated with 49% increased likelihood for improvement in 6-minute walk ( P =0.04). Similar model with V-wave change as a dichotomous variable showed that patients with a V-wave decrease of ≥11 mm Hg were 3.8× more likely to improve their 6MWT ( P =0.05). Conclusions—: Acute changes in LA pressure after MitraClip procedure are associated with clinical improvement as measured by 6MWT. Continuous LA pressure monitoring may be a useful tool for procedural guidance during transcatheter mitral repair.